Exploring Somali women's reproductive health knowledge and experiences: results from focus group discussions in Mogadishu. Issue 46 (November 2015) - Gure, Faduma; Yusuf, Marian; Foster, Angel M.
Abstract: With a total fertility ratio of 6.7 children per woman, a maternal mortality ratio over 1, 000 deaths per 100, 000 live births, high rates of sexual and gender-based violence, and the lowest contraceptive prevalence rate in the world, women's reproductive health indices in Somalia prove alarming. The voices of women living in Somalia have long been neglected and we undertook this qualitative study to explore women's reproductive health knowledge and experiences. In 2014, we conducted four focus group discussions with 21 married and unmarried women of reproductive age living in Mogadishu, Somalia. Discussions took place in Somali and we used a constant comparative approach to analyse the discussions for content and themes. Our findings reveal that misinformation, restrictive policies, mistrust of clinicians, and prohibitively expensive services shape women's experiences and health-seeking behaviours. Women identified the need for culturally resonant reproductive health information and services as a significant priority. As Somalia begins to emerge from over two decades of civil war, it is imperative that comprehensive reproductive health issues are included on the national agenda and that women's perspectives are incorporated into future policies and interventions. Résumé: Avec un taux de fécondité total de 6, 7 enfants par femme, un taux de mortalité maternelle supérieur à 1000 décès pour 100 000 naissances vivantes, des proportions élevées de violence sexuelle et sexiste et le plus faible taux d'utilisation de contraceptifs au monde, les indicateurs de la santé génésique des femmes en Somalie sont préoccupants. Nous avons entrepris cette analyse qualitative pour étudier les connaissances et les expériences des femmes en matière de santé génésique. En 2014, nous avons organisé quatre discussions de groupe avec 21 femmes mariées et célibataires en âge de procréer qui vivaient à Mogadiscio (Somalie). Les discussions se sont déroulées en somali et nous avons utilisé une approche comparative constante pour analyser le contenu et les thèmes des discussions. Nos conclusions ont révélé que la désinformation, les politiques restrictives, la méfiance à l'égard des cliniciens et le coût prohibitif des services façonnent les expériences des femmes et leur comportement de recherche de soins. Les femmes ont jugé que le besoin d'informations et de services de santé génésique culturellement adaptés était une priorité. Les voix des femmes vivant en Somalie sont depuis longtemps négligées. Alors que la Somalie commence à émerger de plus de vingt années de guerre civile, il est impératif d'inclure des questions globales de santé génésique à l'ordre du jour national et d'intégrer les perspectives des femmes dans les futures politiques et interventions. Resumen: Con una tasa de fertilidad total de 6.7 hijos por cada mujer, una razón de mortalidad materna de más de 1000 muertes por cada 100, 000 nacidos vivos, altas tasas de violencia sexual y violencia de género, y la menor tasa de prevalencia de uso de anticonceptivos del mundo, los índices de salud reproductiva de las mujeres en Somalia son alarmantes. Desde hace mucho tiempo, se hace caso omiso a las voces de mujeres que viven en Somalia. Llevamos a cabo este estudio cualitativo para examinar los conocimientos y experiencias de salud reproductiva de las mujeres. En 2014, realizamos cuatro discusiones en grupos focales con 21 mujeres casadas y solteras en edad reproductiva, que vivían en Mogadishu, en Somalia. Las discusiones se llevaron a cabo en somalí y utilizamos un enfoque comparativo constante para analizar el contenido y las temáticas de las discusiones. Nuestros hallazgos revelan que la información incorrecta, políticas restrictivas, desconfianza en médicos y servicios prohibitivamente caros afectan las experiencias de las mujeres y sus comportamientos con relación a la búsqueda de servicios de salud. Las mujeres identificaron como una prioridad significativa la necesidad de recibir información y servicios de salud reproductiva culturalmente resonantes. A medida que Somalia empieza a emerger de más de dos décadas de guerra civil, es imperativo incluir en la agenda nacional asuntos relacionados con la salud reproductiva integral e incorporar las perspectivas de las mujeres en futuras políticas e intervenciones.